A Multi-interlayer LMAS Joint of C/C–SiC Composites and LAS Glass Ceramics. Issue 5 (May 2015) - Fu, Qiangang; Zhao, Fengling; Li, Hejun; Peng, Han; Nan, Xiaoying
Abstract : Porous C/C–SiC composites were prepared through a two-step chemical vapor infiltration process, and a multi-interlayer joint of Li2 O–MgO–Al2 O3 –SiO2 (LMAS) was applied to join C/C–SiC composites and lithium aluminum silicate (LAS) glass ceramics by means of a vacuum hot-pressing technique. Plenty of SiC whiskers were generated in the pores of low-density C/C composites during chemical vapor deposition process, which is essential to form a zigzag interface structure between C/C–SiC substrate and the LMAS interlayer. The average shear strength of the LMAS joint was improved from 12.17 to 19.91 MPa after changing the composites from high-density C/C composites (1.75 g/cm 3 ) with a CVD-SiC coating to the C/C–SiC composites with a low density (1.48 g/cm 3 ). The improvement of the joint strength is mainly attributed to the formation of the inlay structure at the SiC–C/C and SiC–LMAS interfaces.